2021
DOI: 10.1001/jamaophthalmol.2021.1557
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Visual Impairment and Depression in Patients Attending Eye Clinics

Abstract: IMPORTANCE Given that depression is treatable and some ocular diseases that cause visual loss are reversible, early identification and treatment of patients with visual impairment who are most at risk of depression may have an important influence on the well-being of these patients.OBJECTIVE To conduct a meta-analysis on the prevalence of depression in patients with visual impairment who regularly visit eye clinics and low vision rehabilitation services.DATA SOURCES MEDLINE (inception to June 7, 2020) and Emba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 80 publications
(439 reference statements)
1
37
0
1
Order By: Relevance
“…A possible explanation for this finding is the fact that our sample size was relatively small to allow us to detect a significant effect for depression. On a larger sample of eye disease patients, we could expect less statistical noise and the effect of depression on patients’ quality of life to be stronger, as suggested by previous studies 4 , 5 , 8 . Another plausible hypothesis to explain these findings is the possible indirect effect of visual acuity on depression.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…A possible explanation for this finding is the fact that our sample size was relatively small to allow us to detect a significant effect for depression. On a larger sample of eye disease patients, we could expect less statistical noise and the effect of depression on patients’ quality of life to be stronger, as suggested by previous studies 4 , 5 , 8 . Another plausible hypothesis to explain these findings is the possible indirect effect of visual acuity on depression.…”
Section: Discussionmentioning
confidence: 66%
“…Chronic eye diseases, including AMD and DR, are associated with increased risk for mental health problems, particularly depression which is likely to affect 1.59 times more eye disease patients than healthy controls (OR 1.59; 95% CI 1.40–1.81) 4 . Among eye disease patients, depression has an estimated prevalence of 25%, as shown in two meta-analysis 4 , 5 . Anxiety is also highly prevalent in eye disease patients, with a previous systematic review suggesting a prevalence rate ranging from 9.6 to 30% among AMD patients 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 Two recent meta-analyses of studies of patients receiving eye care services found that the pooled prevalence of depression in patients with vision problems was as high as 25%; the prevalence did not vary by severity of vision impairment but was found in patients visiting both eye clinics and rehabilitation centres. 7 , 8 In China, results from a 16-y longitudinal study also showed unoperated cataract was associated with an increased risk of developing depression over time, and was similar among both males and females, and older and younger patients. 9 However, the relationship between vision impairment and mental health in LMICs, and the effect of gender and age on this relationship, is not well explored.…”
Section: Introductionmentioning
confidence: 99%
“…Eye conditions and vision impairments are associated with many negative consequences such as vision loss, psychological distress, impaired everyday functioning, social isolation and loneliness, uncertainty in illness, and deteriorated socioeconomic status; therefore, compared to normally-sighted persons, persons with eye conditions and vision impairments are more likely to develop mental health problems, in particular depression (1,(6)(7)(8)(9)(10). For example, the prevalence rates of depressive symptoms in middle-aged and older adults with glaucoma, patients with cataracts, patients attending eye clinics, patients with chronic thyroid eye disease, patients with legal blindness, attendees at low-vision rehabilitation centers, and patients with dry eye disease are 10.9, 23.9, 25.0, 28.0, 29.0, 43.0, and 61.0%, respectively (11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%